The Relationship Between Parenting Style And Mental Health In Adolescents - Ni Luh Santhi Putri Wulandari; Ni Komang Sukra Andini; I Dewa Gede Candra Dharma (Journal Nursing Research Publication Media (NURSEPEDIA), 2026)
Background: Adolescence was a developmental phase that was vulnerable to mental health disorders due to physical, social, and emotional changes. Parenting style was an important factor that influenced adolescents' ability to manage pressure and shape their character. Objective: This study aimed to determine the relationship between parenting style and mental health among adolescents at Public Senior High School 2 North Kuta. Method: The research method used was an analytical correlational design with a cross-sectional approach. The study population consisted of all students in grades X–XII, totaling 1,010 respondents, and the sample was determined using purposive sampling with 287 respondents. Data were collected using the parental bonding instrument questionnaire for parenting variables and the MHI-38 for mental health variables, which had been tested for validity and reliability, then analyzed using the Spearman rank correlation test. Result: The results showed that most respondents were 16 years old (36.2%), female (60.3%), and had parents with a senior high school education background (57.1%). Most respondents experienced democratic parenting (48.1%) and had very good mental health (42.5%). The analysis showed a p-value of 0.000 with a correlation coefficient of 0.764, indicating a strong and significant relationship between parenting style and adolescent mental health. Conclusion: These findings indicated that the better the parenting style applied, the better the adolescents' mental health condition, demonstrating that family support played an important role in shaping adolescent psychological well-being.